SLAP: A Secure and Lightweight Authentication Protocol for machine-to-machine communication in industry 4.0. (March 2022) - Panda, Suryakanta; Mondal, Samrat; Kumar, Neeraj
Abstract: Fourth industrial revolution aims to provide a platform which enables machines to collect data, analyze them and make an appropriate decision. Machine-to-machine communication in industry 4.0 helps in better decision-making by monitoring and analyzing different real-time data. Internet Engineering Task Force defines a standard '6LoWPAN' to promote such type of machine-to-machine communication. Although 6LoWPAN attempts to solve important issues, security is not properly addressed and is a major concern during communication. To improve the security and efficiency in the existing state of the arts, we have proposed SLAP, a new secure and lightweight authentication protocol using only hash operation and XOR operation. Our analysis demonstrates that the proposed protocol is safe with respect to various known attacks (i.e., replay attack, man-in-the-middle attack, impersonation attack, modification attack, tracing attack) and efficient compared to the existing state of the arts.